2021
DOI: 10.3389/fimmu.2021.661357
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase 1 Inhibitor-Loaded Nanosheets Enhance CAR-T Cell Function in Esophageal Squamous Cell Carcinoma

Abstract: In chimeric antigen receptor (CAR)-T cell therapy, the role and mechanism of indoleamine 2, 3 dioxygenase 1 (IDO1) in enhancing antitumor immunity require further study. IDO1 is one of the most important immunosuppressive proteins in esophageal squamous cell carcinoma (ESCC). However, the IDO1 inhibitor, epacadostat, has failed in phase III clinical trials; its limited capacity to inhibit IDO1 expression at tumor sites was regarded as a key reason for clinical failure. In this study, we innovatively loaded the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…These results suggest that DNAJC5B may be related to the function, activation state, and role in anti-tumor immune responses of CD8 + T cells. Moreover, this discovery offered crucial insights for the development of novel immunotherapeutic strategies for esophageal cancer, especially in terms of utilizing or targeting CD8 + T cells, consistent with the ndings of other researchers [23].…”
Section: Discussionsupporting
confidence: 84%
“…These results suggest that DNAJC5B may be related to the function, activation state, and role in anti-tumor immune responses of CD8 + T cells. Moreover, this discovery offered crucial insights for the development of novel immunotherapeutic strategies for esophageal cancer, especially in terms of utilizing or targeting CD8 + T cells, consistent with the ndings of other researchers [23].…”
Section: Discussionsupporting
confidence: 84%
“…With the utilizing of epacadostat-loaded hyaluronic acid-modified nanomaterial graphene oxide (HA-GO) nanosheets, CAR-T cells exhibit a more powerful anti-tumor ability. [76] To overcome the immunosuppressive impact of TME with high concentrations of Kyn, Yang et al [77] have modified CAR-T cells through overexpression (OE) of KYUN. They found that KYUN-OE CAR-T cells showed a superior anti-tumor activity even in the immunosuppressive TME with high Kyn.…”
Section: Strategies For Improving the Effectiveness Of Car-t Cells By...mentioning
confidence: 99%
“…Enhanced MUC1-CAR T cells have been shown to have better antitumor activity because they can survive longer in vivo , which means they have long-lasting antitumor effects ( 156 ). Also, it has been recently reported that IDO1 inhibitor-loaded nanosheets could enhance CAR T-cell effectiveness in ESCC and CD276 suppress CAR T-cell function ( 157 , 158 ). The selection of different solid tumor-specific antigens and the delivery of CAR T cells are still the disadvantages of CAR T-cell therapy ( 159 ).…”
Section: Targeting Tumor Microenvironment For Esophageal Squamous Cel...mentioning
confidence: 99%